(untitled) (Research, Society and Development, 2022)
In the COVID-19 pandemic, there was an evident increase in fear and uncertainties, so the vulnerability of pregnant women to the development of psychological disorders, such as Obsessive Compulsive Disorder (OCD), Anxiety, Insomnia and Depression. In order to gain knowledge on the subject, this research was applied to 150 pregnant women admitted to a maternal and child hospital in the state of Pará, so that a gynecological-obstetric profile can be traced and the mental health of pregnant women can be discussed. The predominant age group was 28 to 30 years (40.66%) in which there was the development of stress, depression, insomnia and anxiety. When evaluating the knowledge of pregnant women about the concept of psychological aspects, it was found that a total of 90 (60%) pregnant women knew how to conceptualize. Regarding the analysis of the amount of development of psychological disorders, it is highlighted that 71(47.33%) pregnant women presented stress as the most frequent aspect, followed by anxiety with a total of 56(37.33%) pregnant women, the insomnia totaled 55 (36.67%) pregnant women, 11(7.33%) women with depression were identified, there was no report of OCD and there were 43(28.67%) pregnant women who did not develop any type of psychological disorder during this period. gestational period and the COVID-19 pandemic. It is concluded that the gestation process interferes in pregnant women in different ways, and there is also an influence of the current context of the COVID-19 pandemic. The multiprofessional team must be able to serve this public, aiming at a humanized service so that there is health promotion in an integral way.